Glandular trichomes in the tree-basil (Ocimum gratissimum L., Lamiaceae): Morphological features with emphasis on the cytoskeleton - Tozin, Luiz Ricardo dos Santos [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Elsevier, 2019)
The morphology, histochemistry and ultrastructure of glandular trichomes have been studied in several plant species and their subcellular features are closely related to the composition of the secretion produced. Recent studies have proposed a fundamental role for cytoskeletal elements in the intracellular processes of secretion, culminating with storage of the exudate in cellular compartments or its extracellular release. However, this topic has been poorly studied in plant secretory cells. Ocimum gratissimum L. (Lamiaceae) is an aromatic species widely utilized as a condiment and in popular medicine. Here, we analyzed the distribution, morphology and histochemistry of the glandular trichomes in O. gratissimum, highlighting the distribution of the microtubules and actin filaments in the different glandular morphotypes. Glandular trichomes were observed in the stem, leaves, bracts, sepals and adaxial surface of the petals. Three morphotypes of glandular trichomes were identified and found to secrete different categories of chemical compounds. Plastids devoid of grana and smooth endoplasmic reticulum were abundant in cells secreting lipophilic substances. In these cells, microtubules were intensively labeled. Cells producing mainly hydrophilic compounds were characterized by the presence of dictyosomes with vesicles sprouting. Actin filaments were strongly marked in these cells. Our convergent techniques in microscopy enabled us to establish an association among the glandular morphotypes, their subcellular aspects, the prevalence of the different cytoskeletal elements in their cells and the composition of the secretion produced by them.
Keywords: Actin filaments; Glands; Microtubules; Secretion; Subcellular features